2016
DOI: 10.3390/su8070626
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Judgment and Moral Reaction to the Product-Harm Crisis: Theoretical Model and Empirical Research

Abstract: Based on the dual-process theory of ethical judgment, a research model is proposed for examining consumers' moral reactions to a product-harm crisis. A national-wide survey was conducted with 801 respondents in China. The results of this study indicate that consumers will react to a product-harm crisis through controlled cognitive processing and emotional intuition. The results of the study also show that consumers view a product-harm crisis as an ethical issue, and they will make an ethical judgment according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…In addition, after studying a Korean case, the intensity of this transferring mechanism was shown to differ from industry to industry. Lu et al [28] examined consumers' moral reactions to a product-harm crisis. After conducting a national-wide survey with 801 respondents in China, they found that consumers will react to a product-harm crisis through controlled cognitive processing and emotional intuition.…”
Section: Competitive and Sustainable Manufacturing Approachesmentioning
confidence: 99%
“…In addition, after studying a Korean case, the intensity of this transferring mechanism was shown to differ from industry to industry. Lu et al [28] examined consumers' moral reactions to a product-harm crisis. After conducting a national-wide survey with 801 respondents in China, they found that consumers will react to a product-harm crisis through controlled cognitive processing and emotional intuition.…”
Section: Competitive and Sustainable Manufacturing Approachesmentioning
confidence: 99%
“…Crisis communication includes various ethical aspects, such as having a moral duty to address safety issues and providing an opportunity for stakeholders to acknowledge corporate core values (Sellnow and Seeger, 2013). A few empirical studies (Cheng and Shen, 2020;Lu et al, 2016) emphasized the meaning of ethical judgment (EJ) in organizational crisis communication. Particularly, EJ refers to "an individual's personal evaluation of the degree to which some behavior is ethical or unethical" (Hopkins and Deepa, 2018, p. 504).…”
Section: Literature Review Crisis Communication Timing Strategies: Va...mentioning
confidence: 99%
“…Previous research has found that perceived severity and consumer affect influence consumer reactions [31,32]. According to previous researches [12,33], consumers will experience an emotional reaction to a crisis, which in turn shapes the evaluations of the organization's recovery efforts [34] and organizational reputation [35]. In addition, Cox et al [36] proposed that positive affect does have an influence on consumers' response to drug product risk information.…”
Section: Studymentioning
confidence: 99%